VARIABEL-VARIABEL YANG MEMPENGARUHI KINERJA PADA PERUSAHAAN-PERUSAHAAN DI INDONESIA - Suwondo, Chandra (JMBA Jurnal Manajemen dan Bisnis, 2015)
Whereas many other variables that can affect and improve performance (according to Armstrong) are ones involving Individual Factor, Leadership Factor, Working Group Factor, System Factor and Situation Factor. Applying particularly to enterprises in Indonesia, Performance Variables (Dependent Variable) influenced by Independent Variable are given as: "Formal Education" (X1), "Skills / Expertise" (X2), "Personal Motivation" (X3), "Personal Commitment" (X4), "Private Ideology" (X5), "Ideal Distance from House and Work Locations" (X6), "State of Health" (X7), "Working Age" (X8), "Gender" (X9), "Family harmony" (X10 ), "Family Economic" (X11), "Interest in the Work" (X12), "Leadership" (x13), "Work Culture" (X14), "Family Event" (X15), "Religious Activity" (X16), "Gender Balance "(X17)," Motivation Poster "(X18),"Tolerance Greeting Poster"(x19), Magazine Wall" (X20), "Automation" (X21), "Computerized" (X22), "Outsourcing" (X23), "Compensation" (X24), "Temperature, Circulation, Lighting and Noise at Working Space" (X25), "Instrumental Music" (X26), "Cleanliness of Work Space and Infrastructure" (X27), "Places of Worship" (X28) "Canteen for Eat" (X29) "Good National Economic Growth" (X30), "Good Political Circumstances" (X31), "Good Socio-Cultural Situation" (X32) and others. Of course, the influence of Independent Variables, depends on the type and scale of the related company, not all of the above variables should be discussed (as needed). In one firm, the influence of one Independent Variable may be significant, but on the type and scale of other companies it may not be significant. In general, Performance is the "Desired Result" of the process in the completion of work, the behavior of workers and the necessary conditions. The success of the company's performance, as too the success of the family, is the core of the harmony of all individuals and all factors influencing it.